The use of CellaVision competency software for external quality assessment and continuing professional development. Issue 7 (22nd April 2011) - Horiuchi, Yuki; Tabe, Yoko; Idei, Mayumi; Bengtsson, Hans-Inge; Ishii, Kiyoshi; Horii, Takashi; Miyake, Kazunori; Satoh, Naotake; Miida, Takashi; Ohsaka, Akimichi
Abstract : Aims: Quality assessment of blood cell morphological testing, such as white blood cell (WBC) differential and its interpretation, is one of the most important and difficult assignments in haematology laboratories. A monthly survey was performed to assess the possible role of the proficiency testing program produced by CellaVision competency software (CCS) in external quality assessment (EQA) of the clinical laboratories of affiliated university hospitals and the effective utilisation of this program in continuing professional development (CPD). Methods: Four monthly proficiency surveys were conducted in collaboration with four clinical laboratories affiliated with the teaching hospitals of Juntendo University of Medicine in Japan. Results: EQA results by the CCS proficiency testing program revealed a difference of performance levels of WBC differential and morphological interpretation and a discrepancy in the WBC differential criteria among laboratories. With regard to the utilisation of this proficiency program as a tool for CPD, this program successfully improved the performance of the low-scoring laboratories and less experienced individuals. Conclusions: The CCS proficiency testing program was useful for the quality assessment of laboratory performance, for education, and for the storage and distribution of cell images to be utilised for further standardisation and education.